2004
DOI: 10.1161/01.atv.0000107402.79771.fc
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Arterial Thrombosis

Abstract: Abstract-Arterial thrombosis is a complex disorder that involves multiple genetic and environmental factors interacting to produce the characteristic phenotype. In the past decades, investigators have focused on the molecular genetics of arterial vascular disorders and have identified numerous polymorphisms and mutations in genes related to the hemostatic system and to enzymes involved in the synthesis and bioavailability of nitric oxide (NO); however, the relation between most polymorphisms and the risk of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(127 citation statements)
references
References 159 publications
3
112
0
10
Order By: Relevance
“…Examples of genomic, proteomic, and metabolomic attempts to classify and diagnose vascular diseases already exist. [23][24][25] This tortuous path urgently needs to be taken.…”
Section: Death" -Leo Tolstoy the Death Of Ivan Ilyitchmentioning
confidence: 99%
“…Examples of genomic, proteomic, and metabolomic attempts to classify and diagnose vascular diseases already exist. [23][24][25] This tortuous path urgently needs to be taken.…”
Section: Death" -Leo Tolstoy the Death Of Ivan Ilyitchmentioning
confidence: 99%
“…8 Available data suggest that a single genetic susceptibility factor may have an important impact on the occurrence of arterial thrombosis only when combined with other genetic and/or acquired risk factors. 11,14,19 On the other hand, there is also evidence that inherited thrombophilic states play a significant role precisely among patients with a low a priori cardiovascular risk profile (eg, young, female, without traditional cardiovascular risk factors). In these cases, it is conceivable that as yet unrecognized or poorly appreciated genetic and/or acquired/environmental conditions interact with the known inherited variants to promote arterial thrombosis.…”
Section: Inherited Disorders Of the Hemostatic System Predisposing Tomentioning
confidence: 99%
“…Though several small studies have suggested a role in select populations, particularly in children and in young women with myocardial infarction, 2,3 no effect has been seen in a number of larger studies, 4 including the Physicians' Health Study. 5 The general conclusion has been that these common genetic variants are not major risk factors for myocardial infarction, stroke, or any other form of arterial thrombosis.…”
Section: Factor V Leiden and Other Thrombophilic Mutationsmentioning
confidence: 99%